Long distance transport of irradiated male Glossina palpalis gambiensis pupae and its impact on sterile male yield - Soumaïla Pagabeleguem; Momar Talla Seck; Baba Sall; Marc JB Vreysen; Geoffrey Gimonneau; Assane Gueye Fall; Mireille Bassene; Issa Sidibé; Jean-Baptiste Rayaissé; Adrien MG Belem; Jérémy Bouyer (Parasites & Vectors, 2015)
Abstract Background The application of the sterile insect technique (SIT) requires mass-production of sterile males of good biological quality. The size of the project area will in most cases determine whether it is more cost effective to produce the sterile flies locally (and invest in a mass-rearing facility) or import the sterile flies from a mass-rearing facility that is located in another country. This study aimed at assessing the effect of long distance transport of sterile male Glossina palpalis gambiensis pupae on adult male fly yield. Methods The male pupae were produced at the Centre International de Recherche-Développement sur l’Elevage en zone Subhumide (CIRDES), Bobo-Dioulasso, Burkina Faso, and shipped with a commercial courier service in insulated transport boxes at a temperature of ±10°C to Senegal (±36 h of transport). Upon arrival in the insectary in Dakar, the pupae were transferred to an emergence room and the flies monitored for 3–6 days. Results The results showed that the used system of isothermal boxes that contained phase change material packs (S8) managed to keep the temperature at around 10°C which prevented male fly emergence during transport. The emergence rate was significantly higher for pupae from batch 2 (chilled at 4°C for one day in the source insectary before transport) than those from batch 1 (chilled at 4°C for two days in the source insectary before transport) i.e. an average (±sd) of 76.1 ± 13.2% and 72.2 ± 14.3%, respectively with a small proportion emerging during transport (0.7 ± 1.7% and 0.9 ± 2.9%, respectively). Among the emerged flies, the percentage with deformed (not fully expanded) wings was significantly higher for flies from batch 1 (12.0 ± 6.3%) than from batch 2 (10.7 ± 7.5%). The amount of sterile males available for release as a proportion of the total pupae shipped was 65.8 ± 13.3% and 61.7 ± 14.7% for batch 1 and 2 pupae, respectively. Conclusions The results also showed that the temperature inside the parcel must be controlled around 10°C with a maximal deviation of 3°C to maximize the male yield.